Application of infoworks modeling for flood mapping of Maong River - Jenny Kuihoon, Anak Kulu (UNIMAS, 2006)
InfoWorks River System (RS) Version 5.0is a powerful open channel simulation engine, and is able to handle a wide range of channel shapes, sizes and gradients. The main purpose of this study is to apply the InfoWorks River System (RS) Version 5.0, for mapping the flood area in Maong River, one of the tributaries of Lower Sarawak River. Two scenarios were applied, which are the flood area due to external flood and high tide from the Sarawak Riverand the other is the flood area due to internal storm in catchment. InfoWorks RS, coupled with its embedded Geographical Information System (GIS) application has been used in this study to capture the hydraulic response of the Maong River and its floodplains conditions. Data requirement, preparation,and details on modeling approach are presented. Finally,a discussion of the project limitation and recommendation for further application is given to conclude this project.